Anti-Inflammatory Activities of Leaf Oil from Cinnamomum subavenium In Vitro and In Vivo. (20th February 2019) - Hao, Xincai; Sun, Weiguang; Ke, Changbin; Wang, Fuqian; Xue, Yongbo; Luo, Zengwei; Wang, Xuanbin; Zhang, Jinwen; Zhang, Yonghui
Abstract : The study determined the chemical constituents and anti-inflammatory effects of leaf oil from Cinnamomum subavenium (CS-LO) that has been used in folk medicine to treat various symptoms including inflammation. The anti-inflammatory effects of the oil were evaluated by LPS-stimulated RAW264.7 cells and the Carr-induced hind mouse paw edema model, respectively. In vitro, nitric oxide (NO), prostaglandin E2 (PGE2 ), TNF- α, IL-6, and IL-1 β were significantly decreased by CS-LO, and the expression of nuclear factor- κ B (NF- κ B) protein was blocked as well. In in vivo, the malondialdehyde (MDA) and paw edema levels were decreased by CS-LO, and the same result came up on the NO and tumor necrosis factor (TNF-a) of serum at the 5th h after Carr injection. In addition, iNOS and COX-2 immunoreactive cells of the paw tissue were decreased significantly by CS-LO (200 mg/kg) in histological examination. The present findings indicated that CS-LO have anti-inflammatory properties, and the effects might be caused through inhibiting iNOS, COX-2, TNF- α, IL-1 β, and IL-6 expression via affecting NF- κ B pathway, which will provide a power scientific basis for CS-LO to be used as the treatment of inflammatory diseases.